2017
DOI: 10.1002/dvdy.24548
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment and noncoding RNAs as co‐drivers of epithelial–mesenchymal transition and cancer metastasis

Abstract: Reciprocal interactions between cancer cells and tumor microenvironment (TME) are crucial events in tumor progression and metastasis. Pervasive stromal reprogramming of TME modifies numerous cellular functions, including extracellular matrix (ECM) stiffness, inflammation, and immunity. These environmental factors allow selection of more aggressive cells that develop adaptive strategies associating plasticity and epithelial-mesenchymal transition (EMT), stem-like phenotype, invasion, immunosuppression, and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 300 publications
(341 reference statements)
0
22
0
Order By: Relevance
“…Increased ECM deposition leads to renal fibrosis. It has been reported that noncoding RNAs (ncRNAs) are new participants in the induction and regulation of EMT and kidney fibrosis (9,10). Therefore, it is meaningful to explore the roles of ncRNAs in the molecular mechanisms of EMT and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ECM deposition leads to renal fibrosis. It has been reported that noncoding RNAs (ncRNAs) are new participants in the induction and regulation of EMT and kidney fibrosis (9,10). Therefore, it is meaningful to explore the roles of ncRNAs in the molecular mechanisms of EMT and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activation of NF-κB underlies various human disorders including cancer [ 13 ], and has become one of the major targets for drug development [ 14 , 15 ]. For instance, siRNA mediated disruption of NF-κB significantly suppressed migration and invasion of ESCC cells though attenuation of the epithelial mesenchymal transition (EMT) [ 16 ], the initial step for tumor metastasis [ 17 ]. Recently, a long non-coding RNA (lncRNA) NKILA (nuclear transcription factor NF-κB interacting lncRNA) which could mask the phosphorylation site of IκB, inactivate the NF-κB signaling and suppress breast cancer metastasis [ 18 ] has attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…ECM selects survival cancer cells to aid in tumor growth and invasion at the fastest rate. ECM can also affect tumor development and metastasis through extracellular secretion, or by altering the phenotype of stromal cells or cancer cells [3].…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Within this dynamic space, exchange of numerous molecular information is associated with the transition into tumorigenic microenvironment and includes growth factors (GFs), cytokines, chemokines, enzymes, matrix proteins, and metabolic intermediates. Recruitment, activation, reprogramming, and persistence of stromal and immune/inflammatory cells in the extracellular space are the consequences of a reciprocal interaction between TME and cancer cells [2,3].…”
Section: Introductionmentioning
confidence: 99%